2016
DOI: 10.1080/15389588.2016.1157592
|View full text |Cite
|
Sign up to set email alerts
|

Can progress in reducing alcohol-impaired driving fatalities be resumed? Results of a workshop sponsored by the Transportation Research Board, Alcohol, Other Drugs, and Transportation Committee (ANB50)

Abstract: Objective Despite successes in the 1980s and early 1990s, progress in reducing impaired driving fatalities in the United States has stagnated in recent years. Since 1997, the percentage of drivers involved in fatal crashes with illegal blood alcohol concentration (BAC) levels has remained at approximately 20% to 22%. Many experts believe that public complacency, competing social and public health issues, and the lack of political fortitude have all contributed to this stagnation. The number of alcohol-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…These may well draw on important lessons from alcohol-impaired driving enforcement strategies. Over the past decades, the prevalence of alcohol-impaired driving, and specifically related crashes/fatalities, have consistently decreased in North America (Fell et al, 2016; Naimi et al, 2018; Teutsch et al, 2018; Yao et al, 2016). This decrease has been mainly attributed to optimized “deterrence”-based enforcement approaches (e.g., more severe penalties, improved detection or apprehension strategies, swifter consequences) combined with systematic negative social norming of “drinking-and-driving” (Babor et al, 2010; Elder et al, 2004; Hyder, 2018; Kilmer & Midgette, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These may well draw on important lessons from alcohol-impaired driving enforcement strategies. Over the past decades, the prevalence of alcohol-impaired driving, and specifically related crashes/fatalities, have consistently decreased in North America (Fell et al, 2016; Naimi et al, 2018; Teutsch et al, 2018; Yao et al, 2016). This decrease has been mainly attributed to optimized “deterrence”-based enforcement approaches (e.g., more severe penalties, improved detection or apprehension strategies, swifter consequences) combined with systematic negative social norming of “drinking-and-driving” (Babor et al, 2010; Elder et al, 2004; Hyder, 2018; Kilmer & Midgette, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the frequency of sobriety checkpoints must be increased, and alcohol ignition interlocks should be required for all alcohol-impaired driving offenders, which is one of the most supported strategies for reducing alcohol-impaired driving. 35 The enforcement with random breath testing is associated with a significant reduction in the rate of alcohol-related crashes. 36 Immediate roadside prohibitions, which aimed to increase the efficiency of police and courts for processing drinking drivers, significantly reduced fatal and injury crashes than non-alcohol-related crashes.…”
Section: Discussionmentioning
confidence: 99%
“…Develop and implement a multi‐component strategy that includes several complementary interventions (Clough & Bird, ; Fell et al, ; Roman, Scherer, Fell, & Taylor, ). McKee et al () identified several strategies that were used in cities that demonstrated the capacity to restrict malt liquor sales, including recruiting persistent leaders with a commitment to neighborhood issues, developing a broad coalition of community support, and shaping messages to win public acceptance.…”
Section: Discussion: Countering the Challengesmentioning
confidence: 99%
“…Evidence of effectiveness does not necessarily mean that these policies are implemented, or if implemented, enforced and sustained (Thomas, Paschall, Grube, Cannon, & Treffers, ; van Hoof and van Velthoven, ). Effective policies may be underutilized (Fell et al, ; Giesbrecht et al, ), guidelines ignored (Grubesic et al, ), or policies contrary to the international evidence implemented (Gruenewald et al, ; Rossow & Buvik, ). We examine key challenges in implementing and sustaining alcohol policies and propose several strategies to counter these challenges.…”
Section: Introductionmentioning
confidence: 99%